Effective engineering properties in the design of storage structures of postharvest dry bean grain - Hakan Kibar; Turgut Öztürk; Kadir Ersin Temizel (Acta Scientiarum. Agronomy, 2014)
Selected engineering properties (physical and mechanical) of dry bean under non-irrigation and drip-irrigation were determined and compared. These properties are necessary for the design of equipments for harvesting, processing, transporting, estimating loads in storage structures for crops and flow problems in silos such as arching, ratholing, irregular flow and segregation. Some engineering characteristics such as: average length, width, thickness, the geometric mean diameter, sphericity, surface area, volume, thousand grain mass (M1000), bulk and true densities, porosity, angle of internal friction, static coefficient of friction, Poisson ratio and pressure ratio were studied. The highest average values for physical properties were recorded at drip-irrigation, the lowest average values at non-irrigation. Differences between both irrigation systems for physical properties were statistically significant, but differences for sphericity of irrigation systems were not significant. The highest average values for mechanical properties (angle of internal friction, static coefficient of friction and pressure ratio) were recorded at drip-irrigation, the lowest average values at non-irrigation. Differences between both irrigation systems for mechanical properties were statistically significant. According to the research results, it is recommended the use of the data obtained from the drip-irrigated plots in the design of handling equipments and storage facilities for dry bean.